(untitled) (World Bulletin of Public Health, 2023)
Nowdays, the problem of diagnosing the etiological factor of intestinal infections is an urgent problem, since the epidemiological process in these infections is accompanied by global transformations in the population of microorganisms, a change in the role of individual pathogens, their virulence and resistance, the spread of pathogens with multiple resistance to antimicrobial drugs. This is due to the fact that, in recent years, the growth of migration processes has been characterized, the structure of food and water consumption is changing, the technology of production, storage and sale of food products is being improved. Thus, in the current new conditions, it is necessary to identify the determinant of the etiological structure, which determines the trends in the development of the epidemic process in intestinal infections